BAIKALIAN OF SIBERIA (850 - 650 MA) - Khomentovsky V.V. (My University, 2002)
The basic stratigraphic domains of the Late Precambrian in Siberia are the Uchur-Yudoma, Baikal-Lena, and Priyenisel-Angara structure-facies areas (SFA) of the periphery of the old Siberian Platform. Correlation of local stratigraphic subdivisions in structure-facies districts and zones of each of them has been refined. This allowed safe correlation of stratigraphic schemes of the above-mentioned SFA, substantiation of their common event framework, and retracing of the Baikalid belt along the whole margin of the southern Siberian Platform. The boundaries of the main stratigraphic subdivisions of the Siberian Neoproterozoic such as Mayaian (Kerpylian + Lakhandinian), Baikalian, Yudomain, or Vendian define principal tectonic rearrangement. These units are separated from the underlying formations by the event boundary having something in common with the Late Grenwill orogeny. The information obtained in Siberia (microfossils, geochronology) testifies to the Upper Riphean age of all the Mayaian (1100-850 Ma). The Baikalian unit (850-650 Ma) is separated from the enclosing stratigraphic subdivisions by the Lower and Upper Baikalian intense tectonic events. The Baikalian geotectonic stage and related Baikalids are meaningful only within its volume. All the mentioned recurrent events result from the interaction of the margin of the Siberian Craton with its surrounding microcontinents and oceanic crust or are related to motion of lithosphere plates. The boundaries dividing the Baikalian and Vendian units into two parts also have an event base. Though the Baikalian unit, like other subdivisions of the General Scale of the Late Precambrian (Riphean and Vendian), was initially substantiated tectonically, now it is characterized by quite a representative set of geochronological and paleontological signatures. Of great importance is that it contains glacial deposits, which is in agreement with the general cooling reflected in the name Cryogenian, the Baikalian-coeval subdivision of the International Precambrian Scale. The Baikalian should be introduced into the General Stratigraphic Scale of the Russian Late Precambrian and into the chronostratigraphic version of the International Scale.